2018
DOI: 10.24940/theijbm/2018/v6/i12/bm1812-029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Employee Counselling Services and Performance of NGOs in Kenya

Abstract: Employee performance is key to the success of many organizations. This service is normally provided by the human resources in that organization. Corporate leaders of business organizations provide employee welfare services among them employee counselling services as a way of either motivating their employees to improve their productivity. However, little information is known about such as employee counselling services by all the stakeholders in NGOs. The primary purpose of this study was to focus on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These findings concur with Bophela and Govender [7] discoveries that social support programs increased performance of teacher and reduced rate of absenteeism. The findings also concur with Lumiti, Wekesa and Omondi [20] discoveries that teacher social support (bereavement contribution, wedding support and anniversary support) led to a sense of belonging among the staff, improved morale and motivation of the staff.…”
Section: Social Support Programs and Teacher Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…These findings concur with Bophela and Govender [7] discoveries that social support programs increased performance of teacher and reduced rate of absenteeism. The findings also concur with Lumiti, Wekesa and Omondi [20] discoveries that teacher social support (bereavement contribution, wedding support and anniversary support) led to a sense of belonging among the staff, improved morale and motivation of the staff.…”
Section: Social Support Programs and Teacher Performancesupporting
confidence: 88%
“…However, the research was done only in a public institution and hence the findings are not generalizable to the private sector. Lumiti, Wekesa and Omondi [20] researched on the impact of teacher social support and performance of NGOs in Kenya and found that teacher social support (bereavement contribution, wedding support and anniversary support) significantly influenced the performance of NGOs in Kenya. However, having been conducted among non governmental organizations, the findings of this study cannot be utilized in the private sector.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to EE, EP factor has received a lot of researches before. In which, the researchers explore the factors affecting EP listing as employee motivation (Chaudhary and Sharma, 2012), economic support (Lumiti et al, 2018), compensation (Jailani and Nawangsari, 2020) and so on. Thereby, it can be seen that not many studies on the effect of EA on EP have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Although employee performance has been concentrated in many exploratory studies, few studies are related to the impact of employer branding. Recently, only a few studies have mentioned the factors affecting employee performance related to employer branding such as: Employee brand equity (Huang & Lai, 2018), Employee economic support (Lumiti et al, 2018), Compensation, competence, leadership (Jailani & Nawangsari, 2020), Internal organizational policies (Makau & Muna, 2020), employer attractiveness (Nguyen & Nguyen, 2022) and so on. Not many current studies explore the direct relationship between employer branding and employee performance while employer branding, an important strategy, helps improve employee satisfaction and engagement in the organization.…”
Section: Introductionmentioning
confidence: 99%